Avaliação da vegetação ribeirinha em resposta à redução da vazão à jusante da UHE Passo São João - Balestrin, Diego (2014)
In front of the current and growing demand for natural resources, especially of the water resources, it seeks to find a way to minimize the impacts caused by the anthropic interference in areas of riparian vegetation. These environments have an important functionality to the ecosystems belonging and surrounding due to the fact of this vegetation possesses intrinsic characteristics and adapted to the hydro and ecological environment. The rivers barring for water use as an energy source (study subject of this work) cause various impacts to the environment, one of the major is the alteration of the natural regime of pulses and often, the reducing the downstream flow of the works. The flow reduction in certain stretches of the waterway, besides requiring an in-depth study about the impacts caused by the reduction of the downstream water level of the utilization section, it becomes essential to the vegetation analysis, soil and local geology. These related factors to the morphophysiological characteristics of the different species found in these locations will determine if the current ecosystem, observed in natural altimetric quotes previously found in the area of riparian vegetation, will be able to adapt to the lower quotes checked after implementation of the barring, in other words, in the stretch of reduced flow (SRF). For determination and differentiation of the vegetation it was necessary the study and development of a methodology of analysis by quotes. This analysis was performed using the points method that consisted of a classification and identification by functional character of the existing plants in three sampling units (SU's) located in the SRF of the hydroelectric unit Passo São João town of Roque Gonzales-RS. Furthermore, were performed the gathering of soil samples in the different quotes of the three SU's for physical and chemical analysis. Thus, it was possible to determine that the soil variable (physical and chemical characteristics), has no significant variation by quotes gap and therefore, are not considered necessary for studies of adaptive variations of the vegetation established there. However, in front of this fact and of the generated results, one can strengthen the hypothesis that the hydrological variable is directly responsible for the adaptive variation of the vegetal species in these areas.